Oculokinetic perimetry for the assessment of visual fields. Issue 4 (April 1990) - Clark, B J; Timms, C; Franks, W A
Abstract : The visual fields of 13 children aged 7 to 16 (mean 10.7 years) were assessed by oculokinetic perimetry (OKP), a technique where the field of vision is tested at reading distance using a simple chart, and the results compared with conventional Goldmann perimetry. Cooperation with testing was greater for OKP than Goldmann perimetry and in some cases OKP was better correlated with clinical findings. The advantages of visual field assessment by OKP for children are the close proximity of observer and child, the absence of the requirement for prolonged fixation, and the inexpensiveness and portability of the testing equipment. The disadvantages are movements of the head, with variability in the distance from the target, and the limitation to the central 25 degrees of the visual field.